2006
DOI: 10.1188/06.onf.127-137
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Review of Lycopene and Breast Cancer

Abstract: The emerging area of health-derived benefits from food sources such as lycopene requires additional inquiry into the examination of physiological and nutritional parameters. Nurses should include antioxidant therapy in their base of knowledge when caring for patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Past research has suggested that lycopene may reduce cancer risks by a variety of mechanisms including the inhibition of cell proliferation (Campbell et al, 2004;Everson and McQueen, 2004;Gann et al, 1999;Giovannucci et al, 2002;Jian et al, 2005;Stahl and Sies, 1996;Wane and Lengacher, 2006;Wertz et al, 2004). The specific mechanism of lycopene is unclear and is made complicated rather than more lucid due to the various in vitro model systems of various investigators (Hantz et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Past research has suggested that lycopene may reduce cancer risks by a variety of mechanisms including the inhibition of cell proliferation (Campbell et al, 2004;Everson and McQueen, 2004;Gann et al, 1999;Giovannucci et al, 2002;Jian et al, 2005;Stahl and Sies, 1996;Wane and Lengacher, 2006;Wertz et al, 2004). The specific mechanism of lycopene is unclear and is made complicated rather than more lucid due to the various in vitro model systems of various investigators (Hantz et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Lycopene, an extract of tomatoes, has been reported to have anti-inflammatory effects via an antioxidative function and has been shown to have a preventive effect in reducing the incidence of chronic diseases such as prostate cancer, breast cancer and cardiovascular diseases [5][6][7]. Recently, the multiple modes of action of lycopene in prostate cancer risk reduction were discussed in a review which stressed that inhibition of inflammation, local androgen signalling, multiple levels of antioxidant defence and reduction of prostate epithelial cell proliferation, all contributed to improving prostate health [8].…”
Section: Introductionmentioning
confidence: 99%
“…Lycopene, a red orange carotenoid that is found primarily in tomatoes, has been reported to have anti-inflammatory effects via an antioxidative function [19] and has been shown to have a positive effect in the treatment of chronic diseases [20,21] . Lycopene, through its multiple modes of action, seems to improve prostate health [22] .…”
Section: Introductionmentioning
confidence: 99%